2006
DOI: 10.1111/j.1365-2095.2006.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Meat and bone meal replacement in diets for juvenile gibel carp (Carassius auratus gibelio): effects on growth performance, phosphorus and nitrogen loading

Abstract: A 11-week growth trial was conducted in a flow-through system with juvenile gibel carp Carassius auratus gibelio to evaluate the effects of gradual replacement of fish meal (FM) by meat and bone meal (MBM) on growth performance, phosphorus (P) and nitrogen (N) loading. Six isonitrogenous (crude protein: 410 g kg . The results showed that the best growth was achieved with fish fed on the control diet and MBM 20 . Final body weight, weight gain, feed efficiency, protein retention efficiency and energy retention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 43 publications
(135 reference statements)
1
20
1
1
Order By: Relevance
“…This result indicates that fishmeal could be replaced with TBM up to 30 % without deterioration of the FCR by the rockfish, as there was an effective improvement in the weight gain of the fish. Similarly, the feed utilization of fish commonly improves when fishmeal is successfully replaced with an alternative animal and/or plant protein sources (Kikuchi 1999;Yang et al 2004;Zhang et al 2006;Guo et al 2007;Kader et al 2011;. No improvement in weight gain, but rather higher FCR and poorer PER of fish that were fed the TBM100-S diet compared to those of fish that were fed the TBM100 diet in our study indicated that there is no promising effect of the additional substitution of soybean meal with TBM.…”
Section: Experimental Dietscontrasting
confidence: 66%
“…This result indicates that fishmeal could be replaced with TBM up to 30 % without deterioration of the FCR by the rockfish, as there was an effective improvement in the weight gain of the fish. Similarly, the feed utilization of fish commonly improves when fishmeal is successfully replaced with an alternative animal and/or plant protein sources (Kikuchi 1999;Yang et al 2004;Zhang et al 2006;Guo et al 2007;Kader et al 2011;. No improvement in weight gain, but rather higher FCR and poorer PER of fish that were fed the TBM100-S diet compared to those of fish that were fed the TBM100 diet in our study indicated that there is no promising effect of the additional substitution of soybean meal with TBM.…”
Section: Experimental Dietscontrasting
confidence: 66%
“…Similarly, Kikuchi et al (1997) showed that growth of olive flounder fed the diets substituting MBM with supplementation of amino acids for 18% fishmeal was comparable to that of fish fed the fishmeal-based diet. Growth of yellowtail (Seriola quinqueradia) and gibel carp (Carassius auratus gibelio) substituting MBM for 20% fishmeal was comparable to that of fish fed the fishmeal-based diet (Shimeno et al 1993;Yang et al 2004;Zhang et al 2006). Dietary substitution of 30 and 24% fishmeal with MBM supplemented with methionine could be made without deterioration of performance of cuneate drum (Nibea miichthioides) and Malabar grouper (Epinephelus malabaricus), respectively (Guo et al 2007; Li et al 2009).…”
Section: Resultsmentioning
confidence: 92%
“…Improvement in PER and/or PR of fish fed the MBM10, MBM20 and PM10 diets in this study indicated that substitution of fishmeal up to 20% MBM and 10% PM in the diets could improve protein utilization of fish, resulted from an effective improvement in weight gain of fish. Similarly, protein utilization of fish commonly improved when fishmeal was replaced with the alternative animal and/or plant protein sources in the diets Kikuchi 1999b;Yang et al 2004;Zhang et al 2006).…”
Section: Resultsmentioning
confidence: 97%
“…In aquaculture, both P and N originate mainly from fish feeds [3] due to their high amounts in fishmeal (FM) that is rich in P [4,5]. Several studies have reported that the high P of fish meal-based diets is not well utilized by many fish species, such as common carp Cyprinus carpio L., gibel carp Carassius auratus gibelio or rainbow trout Onchorhynchus mykiss Walbaum [6][7][8]. As a consequence, P loading into the water by fish is generally high, and thus fishmeal-based-diets are considered as primary pollutants of aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%